2007
DOI: 10.1002/14651858.cd006048.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for men who physically abuse their female partner

Abstract: Co-registration This review is co-registered within both the Cochrane and CampbellCollaborations. A version of this review can also be found in the Cochrane Library. KeywordsContributions Dalsbo and Smedslund wrote the protocol. All reviewers independently screened literature, reviewed potential trials, and extracted data. Smedslund analysed the data. Smedslund wrote the text of the completed systematic review. Dalsbo coordinated and wrote the 2010 updated version. Steiro, Winsvold and Clench-Aas contributed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 16 publications
2
71
0
2
Order By: Relevance
“…24 -26 Motivational interviewing, as discussed by physicians in our sample, has been explored as a possible intervention for IPV perpetrators. 21,[27][28][29] To our knowledge, brief motivational interviewing interventions focused on IPV perpetration in primary care settings have yet to be explored. Additional research should explore the negative impact of IPV perpetration on the abuser, 30,31 as this may be beneficial for the development of effective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…24 -26 Motivational interviewing, as discussed by physicians in our sample, has been explored as a possible intervention for IPV perpetrators. 21,[27][28][29] To our knowledge, brief motivational interviewing interventions focused on IPV perpetration in primary care settings have yet to be explored. Additional research should explore the negative impact of IPV perpetration on the abuser, 30,31 as this may be beneficial for the development of effective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Hacerlo de otra manera hace que las intervenciones tengan poca probabilidad de ser efectivas (24)(25)(26) . Por otra parte, estos resultados plantean el reto de estudiar con mayor profundidad la dinámica y participación de la mujer y el hombre en la violencia de pareja.…”
Section: Discussionunclassified
“…More recent studies and reviews of batterer interventions have reported equivocal or less than robust findings (Corvo, Dutton, & Chen, 2008;Dunford, 2000;Feder & Wilson, 2005;Gondolf, 2007;2011;Jackson et al, 2003;Murphy & Ting, 2010;Saunders, 2008;Smedslund, Dalsbø, Steiro, Winsvold, & Clench-Aas, 2011;Stover, Meadows, & Kaufman, 2009). Jackson et al (2003) reported discouraging BIP results based on randomized trials using large samples from Broward County, Florida, and Brooklyn, New York.…”
Section: This Study Examined Changes In the Beliefs And Behaviors Of mentioning
confidence: 99%
“…Outcomes From a Duluth Model Batterer Intervention Program 5 the follow-up data collection period in the present study was much longer than typically seen even in the few well-conducted trials of BIP effectiveness (Maxwell et al, 2010;Smedslund et al, 2011). Permission was obtained from one of the 42 BIPs in Florida to conduct this evaluation focusing on both short-term attitudinal changes and long-term recidivism outcomes among BIP completers versus noncompleters.…”
Section: Downloaded By [Kainan University] At 13:10 18 February 2015mentioning
confidence: 99%